HETEROGENEOUS REACTIONS RELATED TO ANTARCTIC OZONE HOLE - ハタケヤマ, シロウ /; HATAKEYAMA, Shiro; LEU, Ming-Taun (1987)
P(論文) Reactions of chlorine nitrate (ClONO_2) with HCl and H_2O have been investigated using a 320-L Pyrex chamber and long-path FT-IR spectroscopy. Both reactions showed highly heterogeneous nature. Obtained upper limit rate constants fot homogeneous reactions were 8.4×(10)^<-21> and 3.4×(10)^<-21>(cm)^3 molec^<-1>s^<-1> for ClONO_2+HCl and ClONO_2+H_2O, respectively, at 296±2K at 730 torr total pressure. The yield of HNO_3 from both the reactions was 1.05±0.09 and 0.86±0.08,respectively. Formation of HOCl was confirmed in the latter reaction. No synergistic effect between HCl and H_2O was observed for the reaction with ClONO_2. The kinetic behavior of the reaction ClONO_2+H_2O was well described by simple first-order kinetics while the behavior of the reaction ClONO_2+HCl was found to obey the Langmuir adsorption isotherm. departmental bulletin paper